EKSPERIMEN GELOMBANG BUNYI DENGAN TELEPON KALENG - Dedes Asriani Siregar; Febriani Hastini Nasution; Kartika Situmeang; Jenita Damayanti Hutabarat; Gustin Suci Wulan Dari; Yuli Al Aisyah Harahap; Mardin Lianus Ziliwu (Institut Pendidikan Tapanuli Selatan, 2026)
This community service aims to introduce the basic concept of sound waves to elementary school students through a tin can telephone experiment. The activity was carried out using two tin cans connected by a taut string as a medium for sound propagation. Students were asked to take turns speaking and listening through the tin cans to observe how sound propagates. The results of the study showed that this experimental activity increased students’ understanding of the concept of sound propagation, demonstrated by their ability to explain that vibrations in the tin can are transmitted through the string until they are heard in the receiving tin can. In addition, the experimental activity was proven to increase students’ enthusiasm for learning and engagement in science learning. Thus, the tin can telephone can be used as a simple and effective learning medium to introduce the concept of sound waves to elementary school students. Keywords: observation of sound wave results, student activities